A comparative study on the mechanical and tribological characteristics of AA7075/h-BN and AA7075/h-BN/MoS2 hybrid nano-composites produced using stir-squeeze casting process. (12th August 2021) - Beyanagari, Sudheer Reddy; Kandasamy, Jayakrishna
Abstract: AA7075 is used in several automobile applications due to its low density and better mechanical properties. However, the friction and wear properties of AA7075 are not up to the mark to extend its application for tribological applications. Hence, this present study focuses on improving the mechanical and wear properties of AA7075 through different reinforcements like h-BN and MoS2 nanoparticles. Two different composites namely AA7075/h-BN and hybrid AA7075/h-BN/MoS2 are produced using a stir-squeeze casting process by varying weight percentages of h-BN and MoS2 particles and their mechanical and tribological characteristics are compared. Physical characterization like morphology, phase structure, density, and porosity values are determined. The reinforcement of MoS2 and h-BN particles has modified the microstructure in terms of dendrite formation. Hardness is measured and correlated with the tensile strength of the developed composites. Maximum ultimate tensile strength (UTS) of 361.5 MPa is obtained for AA7075/h-BN composite as compared to hybrid AA7075/h-BN/MoS2 and AA7075. A higher hardness of 164.39 HV is attained for AA7075/1.0h-BN/0.5MoS2 composite as compared to AA7075/h-BN composites and AA7075. Tribological characterization is studied using the pin-on-disc apparatus at an applied load of 40 N, a sliding distance of 1000 m, and a sliding velocity of 2 m s −1 . Higher delamination and adhesion wear exhibited by AA7075 is controlled with the reinforcements of h-BN and MoS2 nanoparticles. Comparatively, the hybrid AA7075/h-BN/MoS2 has shown better tribology behavior than the other composites. Additionally, the various wear mechanisms of AA7075/h-BN and hybrid AA7075/h-BN/MoS2 composites during the sliding are studied.